KECAMATAN TAMPAN OLEH DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA PEKANBARU (Studi Kasus: Pangkalan LPG 3 kg) - Andini Faisal; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
LPG 3 kg has become a very important requirement. It can be seen from the demand for LPG 3 kg is increasing every year, both in use for households or for the development of micro enterprises. The purpose of this research was to determine how the LPG 3 kg distribution control in the Kelurahan Sidomulyo Barat Kecamatan Tampan by the Department of Industry and Trade of Pekanbaru City (case study: Sub Distributor LPG 3 kg) and to determine the factors that affect the control in the distribution of LPG 3 kg.Theoretical concepts used is controlling from Ukas. Indicators in this research accomplished the standard, compare result with standard, and take correction action. And to determine the factors that affect the control in the distribution of LPG 3 kg by the Department of Industry and Trade of Pekanbaru City in Kelurahan Sidomulyo Barat Kecamatan Tampan based on research in the field. The method used is descriptive qualitative with purposive sampling technique . Informants in this study is the Department of Industry and Trade of Pekanbaru City, PT . Pertamina ( Persero ), Distributor LPG 3 kg , Sub- Distributors LPG 3 kg and Consumers with accidental sampling technique .From the research, it can be concluded that controlling is done by Department of Industry and Trade of Pekanbaru City in Kelurahan Sidomulyo Barat Kecamatan Tampan no miximized. can be seen from sub distributors LPG 3 kg that did not apply the Standard Operating Procedure (SOP) one of which is a sub distributors who sells LPG 3 kg over the normal price in the distribution area Kelurahan Sidomulyo Barat Kecamatan Tampan.Keywords: Controlling, Distribution, Sub Distributors LPG 3 kg